Pengaruh Rasio Likuiditas, Solvabilitas, Profitabilitas Terhadap Kinerja Keuangan (Studi Empiris Pada Perusahaan Bank Konvensional Yang Terdaftar di Bursa Efek Indonesia Periode 2018- 2021) - Sri Tyas Listia; Budi Wahono; Ety Saraswati (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study was conducted with the aim of analyzing the effect of Liquidity Ratio with Current Ratio (CR) analysis, Solvency Ratio with Debt Ratio (DR) analysis, and Profitability Ratio with Return On Equity (ROE) analysis on Financial Performance. The population used in this study is banking sector companies, which were listed on the Indonesia Stock Exchange (IDX) during the 2018-2021 period. Sample selection using Purposive Sampling technique. This study used multiple linear regression analysis with hypothesis testing using the t test. The results of this study show that the Liquidity (CR) variable has a significant effect on financial performance. Solvency (DR) has a significant effect on financial performance. And Profitability (ROE) has an insignificant effect on financial performance. Keywords: Liquidity, Solvency, Profitability and Financial Performance.